Knowledge, Attitudes, and Practices Toward COVID-19 Among the General Public in the Border Region of Jazan, Saudi Arabia: A Cross-Sectional Study - Almalki, Mohammed J. (Frontiers in Public Health, 2021)
Background: The Saudi government had implemented unprecedented preventive measures to deal with COVID-19. These measures included intermittent curfews, bans on public gatherings, limitations on many services, temporary suspension of Hajj, Umrah, and visit and launching awareness campaigns. Therefore, this study aimed to assess the KAP toward COVID-19 among residents of the border region of Jazan, Saudi Arabia. Methods: An online cross-sectional survey was distributed from May 4 to May 21, 2020, using a Google Form. The survey questionnaire covered demographic characteristics and KAP toward COVID-19. The KAP questions consisted of 17 items on knowledge, four items on attitude, and six items on practice. Results: A total of 597 participants responded to the survey questionnaire. Overall, participants demonstrated a good knowledge of COVID-19, correctly answering 77% of the knowledge questions. Most of the participants exhibited good attitudes and acceptable practices toward COVID-19. Multiple regression analysis revealed that participants with a university education (B = 1.75) or post-graduate education (B = 2.24), those with an income >SR 10,000–20,000 (B = 1.38) or >SR 20,000 (B = 2.07), and those who had received a personal health education (B = 1.19) had higher COVID-19 knowledge scores (p < 0.05). The ordinal logistic regression analysis found that compared to being female, being male was significantly associated with worrying about COVID-19 (p = 0.024, OR = 1.78), willingness to receive a COVID-19 vaccine (p = 0.003, OR = 1.81), and willingness to report potential symptoms of COVID-19 (p = 0.046, OR = 2.28). Worrying about COVID-19 was significantly associated with pre-university education vs. post-graduate education (p ≤ 0.001, OR = 7.94) and university education vs. post-graduate education (p ≤ 0.001, OR = 4.17). The binary logistic regression analysis found that compared to being female, being male was significantly associated with less face mask wearing in public (p = 0.009, OR = 0.31): Females were 3.23 times more likely to wear a face mask than were males. Conclusions: Most of the study participants had good knowledge, positive attitudes, and effective practices toward COVID-19. The findings of this study may help guide future awareness resources to the groups most in need in the Jazan region, particularly as the COVID-19 situation develops and changes. Further assessment should consider the groups omitted from this study, including immigrants and the elderly who have not adopted social media and technology.